2009
DOI: 10.1093/abbs/gmp078
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of phenoloxidase from <italic>Octopus ocellatus</italic>

Abstract: Phenoloxidase (PO) from ink sacs of Octopus ocellatus was purified by gel-filtration and ion-exchange chromatography, and characterized in terms of its biochemical and enzymatic properties by using L-dihydroxyphenylalanine (L-DOPA) as the specific substrate. It was found that prophenoloxidase from O. ocellatus was isolated as a heterodimeric protein of 153.8 kDa, and two subunits of 75.6 and 73.0 kDa were often detected in preparations after SDS activation. The PO-like activity showed optimal pH of 7.0, optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 32 publications
2
31
0
Order By: Relevance
“…The estimated molecular mass of the purified AsPO was determined to be 125.5 kDa in both reducing and non-reducing SDS-PAGE, which indicated that only one type of active PO in brine shrimp A. sinica. The molecular mass of AsPO is much higher than that of the other Crustacean POs (60-77 kDa) [7,10,11,13 -15,17], and lower than that of heterodimeric proPOs from O. ocellatus (153.8 kDa) [11] and squid Illex argentinus tyrosinase (140.2 kDa) [25]. These results imply that AsPO is different from the other Crustacean POs both in molecular forms and molecular masses.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…The estimated molecular mass of the purified AsPO was determined to be 125.5 kDa in both reducing and non-reducing SDS-PAGE, which indicated that only one type of active PO in brine shrimp A. sinica. The molecular mass of AsPO is much higher than that of the other Crustacean POs (60-77 kDa) [7,10,11,13 -15,17], and lower than that of heterodimeric proPOs from O. ocellatus (153.8 kDa) [11] and squid Illex argentinus tyrosinase (140.2 kDa) [25]. These results imply that AsPO is different from the other Crustacean POs both in molecular forms and molecular masses.…”
Section: Discussionmentioning
confidence: 91%
“…The reaction was stopped and each reaction mixture was measured spectrophotometrically under the same conditions as described above, respectively. To determine the optimal pH value of AsPO activity, the reaction mixture containing 20 ml of 15 mM L-DOPA and 20 ml of the purified AsPO at pH 5.0, 6.0, 7.0, 8.0, and 9.0, respectively, was incubated for 40 min at 288C as described previously [11]. The reaction was stopped and each reaction mixture was measured spectrophotometrically under the same conditions as described above, respectively.…”
Section: Optimal Ph Value and Temperature Determinationmentioning
confidence: 99%
See 3 more Smart Citations